2019
DOI: 10.1101/802934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pseudomonas aeruginosa lasRmutant fitness in microoxia is supported by an Anr-regulated oxygen-binding hemerythrin

Abstract: 1 Pseudomonas aeruginosa strains with loss-of-function mutations in the transcription factor 2 are frequently encountered in the clinic and the environment. Among the characteristics common 3 to LasR-defective (LasR-) strains is increased activity of the transcription factor Anr, relative to 4 their LasR+ counterparts, in low oxygen conditions. One of the Anr-regulated genes that was 5 highly induced in the LasR-strains encoded a putative oxygen-binding hemerythrin encoded by 6 PA14_42860 (PA1673) which we nam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…1E ). We have previously shown that Anr activity is higher in ∆ lasR strains and contributes to the competitive fitness of the ∆ lasR strain against WT P. aeruginosa in colony biofilms ( 27 , 45 ), but Anr was not required for coculture pyocyanin production ( Fig. S2 ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…1E ). We have previously shown that Anr activity is higher in ∆ lasR strains and contributes to the competitive fitness of the ∆ lasR strain against WT P. aeruginosa in colony biofilms ( 27 , 45 ), but Anr was not required for coculture pyocyanin production ( Fig. S2 ).…”
Section: Resultsmentioning
confidence: 93%
“…Planktonic cultures were grown on roller drums at 37°C. Artificial sputum medium (ASM) was made as described previously ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1D ). We have previously shown that Anr activity is higher in Δ lasR strains and contributes to Δ lasR competitive fitness against WT P. aeruginosa in colony biofilms (53, 54), but Anr was not required for co-culture pyocyanin production by Δ lasR ( Fig. S2 ).…”
Section: Resultsmentioning
confidence: 93%
“…There are several possible explanations for this apparent contradiction. Loss of lasR function confers some fitness advantages including altered catabolic profiles (18) and enhanced growth in low oxygen (19, 20). Further, some LasR-strains exhibit rewired regulation of quorum sensing (QS)-controlled exoproducts (21) and LasR-strains can activate QS signaling in response to products from other species (22) or in specific culture conditions (23, 24).…”
Section: Introductionmentioning
confidence: 99%